Pengaruh Kualitas Produk dan Kualitas Pelayanan terhadap Loyalitas Pelanggan PT.Mitra Bangunan Abadi - Sihotang, Darul Ahmadi; Kurnia, Muhammad; Kaidupa, Ismail (BUDGETING : Journal of Business, Management and Accounting, 2024)
PT. Mitra Bangunan Abadi (MBA) is a manufacturer in the piping and other fittings equipment field. Advancements in technology have led to progress in the construction industry, prompting all construction companies to strive for improvement in their product quality and service quality, including PT. Mitra Bangunan Abadi (MBA). Despite having fairly good product quality, products from PT. Mitra Bangunan Abadi (MBA) have not been able to achieve a top brand index in the piping sector in Indonesia. The aim of this research is to understand the depiction of Product Quality and Service Quality variables on Customer Loyalty for PT. Mitra Bangun Abadi products in Bandung City, as well as the relationship and influence of these variables. This research employs a causal descriptive approach using quantitative methods. Data collection techniques include questionnaires and internet research. Probability sampling method with cluster sampling technique is utilized, targeting consumers in Bandung City, resulting in a sample size of 75 respondents. Data is processed using SPSS, followed by validity testing, reliability testing, descriptive analysis, multiple linear regression analysis, simultaneous test (F-test), partial test (T-test), and coefficient of determination test. The results will demonstrate the influence of variables both simultaneously and partially. Keywords: Customer Loyalty, Product Quality, Service Quality.